2022
DOI: 10.1177/17534259221097948
|View full text |Cite
|
Sign up to set email alerts
|

The monocyte activation test detects potentiated cytokine release resulting from the synergistic effect of endotoxin and non-endotoxin pyrogens

Abstract: Pyrogens are classified in two groups, endotoxin pyrogens and non-endotoxin pyrogens (NEPs). The presence of either in parenteral pharmaceuticals or medical devices can cause severe harm to subjects, and when occurring in combination, synergistic potentiation effects can occur. As the standard in vitro pyrogen test, the Limulus Amebocyte Lysate (LAL) assay can detect LPS only, an endotoxin, but not NEPs. We tested whether the Monocyte Activation Test (MAT) that measures IL-6 induction, is suited for detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our standard approach to interrogating these responses is to gradient purify mononuclear cells from whole blood and incubate the cells for 24 h in RPMI containing 1% human serum and various pattern recognition receptor agonists. For this study we exposed cells to a pan-bacterial stimulus comprised of 1 µg/mL lipopolysaccharide (LPS) and 10 8 copies/mL heat-killed Staphylococcus aureus (HKSA) 20 . We found that after 24 h at 37 °C, unstimulated gradient-purified mononuclear cells spontaneously released several cytokines and chemokines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our standard approach to interrogating these responses is to gradient purify mononuclear cells from whole blood and incubate the cells for 24 h in RPMI containing 1% human serum and various pattern recognition receptor agonists. For this study we exposed cells to a pan-bacterial stimulus comprised of 1 µg/mL lipopolysaccharide (LPS) and 10 8 copies/mL heat-killed Staphylococcus aureus (HKSA) 20 . We found that after 24 h at 37 °C, unstimulated gradient-purified mononuclear cells spontaneously released several cytokines and chemokines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, contaminants, such as microbial species and endotoxins, must be prohibited properly, or completely removed. On the other side, the application of additional analysis, e.g., a monocyte activation test, have been attempted to eradicate the presence of non-endotoxin pro-inflammatory contaminants (peptidoglycan) [ 21 ].…”
Section: Characterization Of Mabsmentioning
confidence: 99%
“…Therefore, the detection of LPS becomes imperative in order to assure food safety as well as to prevent fatal illnesses [5] . Due to the substantial risk posed to human health and the highly toxic nature of LPS, numerous analytical techniques have been devised for LPS detection, one of which is the rabbit pyrogen test, [6] the Limulus‐based test, [7] the monocyte activation test, [8] and LPS sensors utilizing LPS binding proteins, peptides, and aptamers to detect the presence of LPS [9–11] . The rabbit pyrogen test holds the distinction of being the initial method approved by the US Food and Drug Administration (FDA).…”
Section: Introductionmentioning
confidence: 99%